Wide-spectrum photodetector constructed on a centimeter-scale flexible SnSe2 film using a new one-step strategy. (27th July 2021) - Weng, S R; Zhen, W L; Yan, X; Yue, Z L; Hu, H J; Xu, F; Zhang, R R; Pi, L; Zhu, W K; Zhang, C J
Abstract: Two-dimensional (2D) materials attached with flexible substrates enable possibilities to apply their superior properties to the rapidly increasing demand for foldable displays and wearable biosensors in the internet-of-things technology. However, previous two-step strategy to construct the flexible devices, namely first obtaining 2D materials elsewhere and then transferring them onto flexible substrates, can cause huge problems, including irreversibly undermining the device performance and limiting the material size. Here we propose a new one-step strategy (other than the liquid phase processing and low temperature synthesis methods), namely directly depositing appropriate 2D materials onto flexible substrates, which involves no transferring and can maintain the crystal quality and properties to the greatest extent. More importantly, this strategy in principle has no limit in the film size, hence removing a main obstacle for the practical use of flexible films, such as complex logic operations and large-area optoelectronic applications. Using this strategy, a centimeter-scale SnSe2 film is directly grown on polydimethylsiloxane, which is characterized as a uniform, out-of-plane oriented and semiconducting film that is robust to deformations. Based on the film, a flexible photodetector is fabricated and distinct photoresponse to a broad spectrum of light (405–830 nm) is observed, with remarkable technical parameters.